The lysosomal Ragulator complex activates NLRP3 inflammasome in vivo via HDAC6. (29th November 2022) - Tsujimoto, Kohei; Jo, Tatsunori; Nagira, Daiki; Konaka, Hachiro; Park, Jeong Hoon; Yoshimura, Shin‐ichiro; Ninomiya, Akinori; Sugihara, Fuminori; Hirayama, Takehiro; Itotagawa, Eri; Matsuzaki, Yusei; Takaichi, Yuki; et al.
Abstract: The cellular activation of the NLRP3 inflammasome is spatiotemporally orchestrated by various organelles, but whether lysosomes contribute to this process remains unclear. Here, we show the vital role of the lysosomal membrane‐tethered Ragulator complex in NLRP3 inflammasome activation. Deficiency of Lamtor1, an essential component of the Ragulator complex, abrogated NLRP3 inflammasome activation in murine macrophages and human monocytic cells. Myeloid‐specific Lamtor1‐deficient mice showed marked attenuation of NLRP3‐associated inflammatory disease severity, including LPS‐induced sepsis, alum‐induced peritonitis, and monosodium urate (MSU)‐induced arthritis. Mechanistically, Lamtor1 interacted with both NLRP3 and histone deacetylase 6 (HDAC6). HDAC6 enhances the interaction between Lamtor1 and NLRP3, resulting in NLRP3 inflammasome activation. DL‐all‐rac‐α‐tocopherol, a synthetic form of vitamin E, inhibited the Lamtor1–HDAC6 interaction, resulting in diminished NLRP3 inflammasome activation. Further, DL‐all‐rac‐α‐tocopherol alleviated acute gouty arthritis and MSU‐induced peritonitis. These results provide novel insights into the role of lysosomes in the activation of NLRP3 inflammasomes by the Ragulator complex. Synopsis: How inflammasome activation is orchestrated by specific organelles remains unclear. Here, the lysosomal Ragulator complex is shown to enhance NLRP3 inflammasome activation via histone deacetylase 6 (HDAC6). Deficiency of Lamtor1, an essential component of the Ragulator complex, abrogated NLRP3 inflammasome activation in vitro and in mice. Lamtor1 interacted with NLRP3 and HDAC6. HDAC6 enhances the interaction between Lamtor1 and NLRP3. DL‐all‐rac‐α‐tocopherol, a synthetic form of vitamin E, inhibited the Lamtor1–HDAC6 interaction, resulting in diminished NLRP3 inflammasome activation. Abstract : The Ragulator complex component Lamtor1 regulates NLRP3 inflammasome activity via the formation of a Lamtor/HDAC6/NLRP3 complex to link lysosomes with inflammasome activation.